Hen 3-860: new southern eclipsing symbiotic star observed in the outburst. Issue 1 (3rd December 2021) - Merc, J; Gális, R; Wolf, M; Velez, P; Bohlsen, T; Barlow, B N
ABSTRACT: Brightening of Hen 3-860, previously classified as an Hα emitter, was detected by the All-Sky Automated Survey for Supernovae (ASAS-SN) survey at the end of the year 2016. We have obtained the first spectroscopic observations of the transient and supplemented them with photometric data from the Digital Access to a Sky Century at Harvard (DASCH) archive of astronomical plates, All-Sky Automated Survey (ASAS), and ASAS-SN surveys. Based on the results of our analysis, we can classify the object as a classical symbiotic star of the infrared type S, consisting of an M2-3 giant with a temperature of T g  ∼ 3550 K, a radius of R g  ∼ 60–75  R ⊙, and a luminosity of L g  ∼ 540–760  L ⊙, and a hot and luminous component ( T h ∼ 1 × 10 5 –2 × 10 5  K and $L_{\rm h}\, \sim 10^3\, L_\odot$ ). The system experienced at least four outbursts in the last 120 years. In addition to the outbursts, its light curves revealed the presence of eclipses of the hot component and its surrounding (relatively cool) shell, which developed during the outburst and redistributed a fraction of the radiation of the hot component into the optical, by the giant, classifying the object as a representative of a group of eclipsing symbiotic stars. The eclipses allowed us to reveal the orbital period of the system to be 602 d.